Asymmetries in social touch—motor and emotional biases on lateral preferences in embracing, cradling and kissing. Issue 3 (3rd May 2020) - Packheiser, Julian; Schmitz, Judith; Metzen, Dorothea; Reinke, Petunia; Radtke, Fiona; Friedrich, Patrick; Güntürkün, Onur; Peterburs, Jutta; Ocklenburg, Sebastian
ABSTRACT: In human social interaction, affective touch plays an integral role to communicate intentions and emotions. Three of the most important forms of social touch are embracing, cradling and kissing. These behaviours have been demonstrated to be lateralized, but the underlying mechanisms are still not well understood. Both motor and emotive biases have been suggested to affect laterality of social touch. We aimed to systematically investigate how motor preferences and emotive biases influence the lateralization of embracing, cradling and kissing within the same sample. Participants performed all three forms of social touch in neutral, positive and negative emotional conditions. Like a previous study, we found a rightward bias for embracing that was modulated by both motor preferences and the emotional content of the situation. Kissing and cradling were not influenced by motor preferences. In general, a negative emotional connotation of the situation led to a reduction of lateral biases in social touch, independent of the individual direction.